2011
DOI: 10.1242/dev.072579
|View full text |Cite
|
Sign up to set email alerts
|

String (Cdc25) regulates stem cell maintenance, proliferation and aging in Drosophila testis

Abstract: SUMMARYTight regulation of stem cell proliferation is fundamental to tissue homeostasis, aging and tumor suppression. Although stem cells are characterized by their high potential to proliferate throughout the life of the organism, the mechanisms that regulate the cell cycle of stem cells remain poorly understood. Here, we show that the Cdc25 homolog String (Stg) is a crucial regulator of germline stem cells (GSCs) and cyst stem cells (CySCs) in Drosophila testis. Through knockdown and overexpression experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
61
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 29 publications
11
61
1
Order By: Relevance
“…Loss of ptc results in ligand-independent Hh signaling (Ingham et al, 1991;Chen and Struhl, 1996). We counted 44.6±1.2 Zfh1-positive, Eyanegative cells in testes from eyaA3-gal4/+ control males (n=20), consistent with the previously reported 36-50 Zfh1-positive cells per testis (Leatherman and Dinardo, 2010;Inaba et al, 2011). Ptc knockdown causes a statistically significant increase in the number of Zfh1-positive, Eya-negative CySCs to 73.2±3.1 (n=15, P<9.7ϫ10 -8 ) (Fig.…”
Section: Hh Levels Control Cysc Numbersupporting
confidence: 86%
“…Loss of ptc results in ligand-independent Hh signaling (Ingham et al, 1991;Chen and Struhl, 1996). We counted 44.6±1.2 Zfh1-positive, Eyanegative cells in testes from eyaA3-gal4/+ control males (n=20), consistent with the previously reported 36-50 Zfh1-positive cells per testis (Leatherman and Dinardo, 2010;Inaba et al, 2011). Ptc knockdown causes a statistically significant increase in the number of Zfh1-positive, Eya-negative CySCs to 73.2±3.1 (n=15, P<9.7ϫ10 -8 ) (Fig.…”
Section: Hh Levels Control Cysc Numbersupporting
confidence: 86%
“…Loss of CycB or excess of CycA causes increased female GSC loss (Chen et al, 2009;Wang and Lin, 2005), and Cdc25/string is required for male GSC maintenance (Inaba et al, 2011). CycE function is required for FSC maintenance, and 537 RESEARCH ARTICLE Cyclin E and stem cell fate analysis of CycE WX in the FSC lineage showed that FSC loss occurs in the absence of follicle cell proliferation defects (Wang and Kalderon, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Other cell cycle-independent roles of cell cycle regulators As mentioned above, cell cycle regulators, including Cdc25, CycB and CycA have been implicated in GSC maintenance (Chen et al, 2009;Inaba et al, 2011;Wang and Lin, 2005), although it remains unclear whether they control stem cell fate independently of the cell cycle. Yet, cell cycle regulators perhaps function outside of the cell cycle more commonly than previously thought.…”
Section: F36mentioning
confidence: 99%
See 1 more Smart Citation
“…These mutant CySCs proliferated better, generating more labeled cells within the clone, which could persist up to 7 or 14 days without dying but did not differentiate ( We note that CySC clones with a proliferation defect can differentiate, as has been shown for CySC clones lacking string (stg), the Drosophila Cdc25 homolog. In fact, CySCs with impaired proliferation cannot be maintained in the niche (Inaba et al, 2011). Therefore, a proliferation defect cannot account for the lack of differentiation of Tor mutant clones.…”
Section: A948vmentioning
confidence: 99%